Teaching Students to Problem Solving in Chemistry on The Basis of Interdisciplinary Connection - Ibodulloyeva M.I; Formanova Sh.B; Saidazimova G.A. (Genius Publishing Group, 2024)
This article provides information about teaching problem solving in chemistry based on interdisciplinary connections. The use of mathematics, physics, biology and geography in the organization of solving problems in chemistry in the process of teaching students is described
Keywords: Interdisciplinary communication; communication with solving problems of chemistry; biology; physics